Linguistic Landscape Variations at the Museum Pusaka Nias of Gunungsitoli City - Yohanna Tatar Siswinda Lombu; Yarman Krisman Gulo; Ester Jelita Mendrofa (Journal on Education, 2024)
Linguistic landscape or LL is the visibility of language on public signs in a particular area. LL can also be found in tourist areas, which can help tourists in obtaining general information in the area. This research reveals the use of language in information in the Museum Pusaka Nias area through landscape linguistics to understand the role and function of language used in semi-public spaces. Using descriptive qualitative research, data was collected through observation, photography and interviews with Museum staff. Based on the results of the research, there are language variations used, namely Nias local language, Indonesian and English. This language variation reflects the museum's role in preserving Nias culture and serving a variety of visitors, both domestic and foreign tourists. In addition, the findings show how different languages function for informational and symbolic purposes, emphasizing cultural preservation, accessibility and identity. The informational function in the linguistic landscape of the Museum Pusaka Nias informs tourists about information in the form of warnings, appeals, instructions and place names. There are also symbolic functions that have relations in the political and cultural fields of Nias society. This research can provide an understanding of how language is used to represent cultural and social identity in public spaces and the importance of language diversity in the Museum Pusaka Nias area.